PROMISING MIXED CROPS OF SUDAN GRASS WITH FORAGE CROPS - Nasiyev B.N. (Academic Journal of Physical and Chemical Sciences, 2020)
An important factor in increasing the efficiency of crop diversification in West Kazakhstan and reducing the dependence of crop productivity on weather conditions is the expansion of crops most adapted to unsustainable humidification of plants such as chickpeas, Sudan grass, sorghum, corn and sunflower. One of the ways to increase the productivity of Sudanese grass is to use its mixed crops with chickpeas, sunflower, corn and sorghum. Mixtures due to the best quality indicators of feed provide the maximum yield of feed units and digestible protein. The article presents research data on the study of mixed crops of Sudanese grass with annual crops in the conditions of the 1st dry-steppe zone of Western Kazakhstan. A comparative test of mixed crops by yield from digestible protein area units revealed the most nutritionally valuable mixtures. So, in the research of 2018-2020, the largest yield for digestible protein was obtained on the variant using sunflower for silage mixed with Sudan grass (1.65 c/ha), slightly lower on the versions of using a mixture of Sudan grass and corn for silage (1.58 c/ha) and a mixture of sorghum and Sudan grass for silage (1.55 c/ha).